Handbook of benzoxazine resins - Ishida, Hatsuo; Agag, Tarek (Elsevier, 2011)
This handbook provides a wide overview of the field, fundamental understanding of the synthetic methods and structure/property correlation, as well as studies related to applications in a wide range of subjects. The handbook also provides 1H and 13C NMR spectra, FTIR spectra, DSC and TGA thermograms to aid in research activities. Additional tables on key NMR and FTIR frequencies unique to benzoxazine, heat of polymerization, Tg, and char yield will greatly aid in the choice of proper benzoxazine for a specific application. Provides thorough coverage of the chemistry and applications of benzoxazine resins with an evidence-based approach to enable chemists, engineers and material scientists to evaluate effectiveness. Features spectra, which allow researchers to compare results, avoid repetition and save time as well as tables on key NMR frequency, IR frequency, heat of polymerization, of many benzoxazine resins to aid them in selection of materials. Written by the foremost experts in the field.